Case report: Urgent surgical management of pediatric clear cell sarcoma of the kidney with atrial obstruction - Alexandra Varga; Gábor Bogáts; Katalin Rácz; Tamás Kovács (Frontiers Media S.A., 2022)
Clear cell sarcoma of the kidney (CCSK) is an uncommon renal neoplasm of childhood. Progression of intracaval or cavoatrial thrombosis is extremely rare and mostly asymptomatic, treated with neoadjuvant therapy followed by surgery. However, in an unstable patient, acute radical surgical intervention is the treatment of choice. We present a 2-year-old girl diagnosed as having a large left kidney tumor and acute cardiac decompensation via cavoatrial thrombotic progression. Urgent radical nephrectomy and removal of tumor thrombus were performed using atriotomy and inferior vena cava (IVC) endarterectomy under cardiopulmonary bypass. Histopathology revealed CCSK. The patient is tumor-free at 9-year follow-up.